Reduced expression of glycolate oxidase leads to enhanced disease resistance in rice - Chern, Mawsheng (PeerJ Inc., 2013)
Glycolate oxidase (GLO) is a key enzyme in photorespiration, catalyzing the oxidation of glycolate to glyoxylate. Arabidopsis GLO is required for nonhost defense responses to Pseudomonas syringae and for tobacco Pto/AvrPto-mediated defense responses. We previously described identification of rice GLO1 that interacts with a glutaredoxin protein, which in turn interacts with TGA transcription factors. TGA transcription factors are well known to participate in NPR1/NH1-mediated defense signaling, which is crucial to systemic acquired resistance in plants. Here we demonstrate that reduction of rice GLO1 expression leads to enhanced resistance to Xanthomonas oryzae pv oryzae (Xoo). Constitutive silencing of GLO1 leads to programmed cell death, resulting in a lesion-mimic phenotype and lethality or reduced plant growth and development, consistent with previous reports. Inducible silencing of GLO1, employing a dexamethasone-GVG (Gal4 DNA binding domain-VP16 activation domain-glucocorticoid receptor fusion) inducible system, alleviates these detrimental effects. Silencing of GLO1 results in enhanced resistance to Xoo, increased expression of defense regulators NH1, NH3, and WRKY45, and activation of PR1 expression.